Pengaruh Pupuk Organik Cair Daun Kirinyu (Chromolaena odorata) Terhadap Pertumbuhan dan Hasil Seledri Pada Tanah Gambut - ongki aleksa, dwi zulfita, agus hariyanti, ongki (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to determine the effect of liquid organic fertilizer on kirinyu leaves on the growth and yield of celery on peat soil. The research was conducted from 10 November 2018 to 09 January 2019 in the experimental garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. The study used a completely randomized design (CRD) method in which the application of organic fertilizer as a single factor. The treament were designed in five level of concentration and 5 treatments with 5 replications and each replication consisted of 4 sample plants. The treatment in question is k1 = 100 ml / liter of water, k2 = 150 ml / liter of water, k3 = 200 ml / liter of water, k4 = 250 ml / liter of water, k5 = 300 ml / liter of water. The variables observed in this study were root volume, leaf chlorophyll content, number of leaf stalks, plant fresh weight and total plant dry weight. Based on the results of the study it can be concluded that the administration of kirinyu leaf POC with a concentration of 300 ml / liter of water showed the best growth in leaf chlorophyll content and total plant dry weight but on the results of celery plants the effective concentration was indicated by giving kirinyu leaf POC 100 ml / liter water. Keywords: kirinyu leaves, peat, liquid organic fertilizer, celery